Variable Clinical Presentations of Left Atrial Myxoma in Malaysia: A Case Series - Ling, Hwei Sung; Kuan, P.X.; Andrew, K; Fong, A.Y.Y. (Hong Kong college of cardiology, 2016)
Introduction and Purpose: Cardiac myxoma is the most common primary tumour of the heart; often missed due to non-specific symptoms. It may lead to disastrous outcome if it is not treated in a symptomatic patient. Transthoracic echocardiogram (TTE) is the usual imaging modality for establishing the diagnosis. Methods: We reviewed the different types of presentations and outcomes of patients presented to Sarawak General Hospital, Malaysia with myxoma in 2015. Results: Case One: A 67-year-old gentleman, initially treated as bronchial asthma, referred to our centre for worsening shortness of breath despite being treated for one week. Chest X-ray (CXR) was unremarkable. Further work- up with TTE showed left atrial mass suggestive of myxoma measuring 4.3 cm x 3.8 cm. Case Two: A 38-year-old lady, with history of ischemic stroke, presented with sudden unilateral limb weakness and fever. No significant neurological deficit but peripheral vasculitic lesions were noted. She was initially investigated for infective endocarditis with embolic event. However, repeated TTE in our centre showed left atrial mass suggestive of myxoma, measuring 2.1 cm x 2.7 cm. Case Three: A 73-year-old previously healthy woman, presented with worsening reduced effort tolerance over the past one month. Examination was suggestive of left heart failure; consistent with CXR findings. Initial TTE showed atrial mass (1.4 cm x 7.2 cm) causing mitral valve obstruction and pulmonary hypertension. Discussion/Conclusion: The diagnosis of atrial myxoma can be ambiguous and may be easily missed, especially when the different clinical presentations are suggestive of other diagnoses. TTE is investigation of choice for diagnosing myxoma in symptomatic patients. Early surgical intervention is warranted for better outcome. Our review showed all tumour excisions were successful and histopathological examinations confirmed myxoma. Although myxoma is histopathologically benign, they can lead to serious complications e.g. embolism and intracardiac obstruction.